Odpowiedzi

2009-11-15T19:02:25+01:00
1. (a+3b)-(4+2a)-(2b+a) a= 0,1
b= (-0,2)

0,1 + 3*(-0,2) -4-2*0,1 - 2*(-0,2) - 0,1=
= 0,1 - 0,6 -4 + 0,2 + 0,4 - 0,1=
= -4


2. 5x-(jedna czwarta -2y)+(-4x+3y)-2

5x +0,25 + 2y -4x - 3y -2=
x - y - 1,75
2009-11-15T19:03:56+01:00
(0,1+2*(-0,2))-(4+2*0,1)-(2*(-0,2)+0,1)*0,1= (0,1-0,4)-4,2-(-0,4+0,1)*0,1=-0,3-4,2-(-0,04+0,01)=-4,5+0,05=-4,45
Najlepsza Odpowiedź!
2009-11-15T19:19:54+01:00
(a+3b)-(4+2a)-(2b+a)=a+3b-4-2a-2b-a=-2a+b-4
-2a+b-4=-2*0,1-0,2-4=-0,2-0,2-4=-4,4

5x-(1/4-2y)+(-4x+3y)-2=5x-1/4+2y-4x+3y-2=x+5y-2 1/4